Malnutrition and sarcopenia: a combined risk factor for vascular calcification and cardiovascular events in hemodialysis patients - Wang, Zitao; Jiang, Lu; Li, Qing; Xu, Rui; Yuan, Yanggang; Mao, Huijuan; Xing, Changying (Frontiers in Nutrition, 2025)
BackgroundHemodialysis (HD) patients are at high risk of vascular calcification (VC) and cardiovascular disease (CVD). The coexistence of sarcopenia and malnutrition, known as malnutrition-sarcopenia syndrome (MSS), may further exacerbate these risks. This study aimed to investigate the prevalence of MSS in HD patients and its association with abdominal aortic calcification (AAC) and major adverse cardiovascular events (MACE).MethodsThis prospective cohort study enrolled 462 maintenance HD patients, who were subsequently stratified into four groups: no sarcopenia-no malnutrition, sarcopenia alone, malnutrition alone, and MSS. Sarcopenia was diagnosed based on the 2019 Asian Working Group for Sarcopenia (AWGS) criteria, and malnutrition was assessed using the Geriatric Nutritional Risk Index (GNRI). AAC was evaluated using lateral abdominal radiographs and scored according to Kauppila’s semiquantitative scoring system. The primary outcome was MACE during a 3-year follow-up period. Multivariable logistic regression and mediation analyses were employed to determine associations and potential mechanisms.ResultsThe prevalence of sarcopenia and malnutrition was 46.3 and 32.0%, respectively, with 18.2% of patients having MSS. MSS was independently associated with increased AAC (OR: 2.157, 95% CI: 1.064–4.373, p = 0.033) and MACE risk (OR: 2.235, 95% CI: 1.192–4.194, p = 0.012). Mediation analysis revealed that AAC severity partially mediated the relationship between MSS and MACE, accounting for 26.7% of the total effect.ConclusionMSS is prevalent in HD patients and is associated with more severe VC and higher cardiovascular risk. Comprehensive nutritional assessment and targeted interventions are needed to address sarcopenia and malnutrition in HD patients to improve their cardiovascular outcomes.